a) 4x^2 - 9 = 0
4x^2 = 9
x^2 = 9/4
x = +/- 3/2
b) 3x^2 = 49
x^2 = 49/3
x = +/- 7/sqrt(3)
x = +/- 7sqrt(3)/3
2007-03-04 17:46:25
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
4x² - 9 = 0
4x² - 9 + 9 = 0 + 9
4x² = 9
4x² / 4 = 9 / 4
x² = 9 / 4
âx² = ± â9 / â4
x = ± 3 / 2
- - - - - - - - -
3x² = 49
3x² / 3 = 49 / 3
x² = 49 / 3
âx² = ± â49 / â3
x = ± 7 / â3
x = ± 7â3 / â3â3
x = ± 7â3 / â9
x = ± 7â3 / 3
- - - - - - s-
2007-03-05 09:06:30
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
Question A
4x² = 9
x² = 9 / 4
x = ± â (9/4) = ± 3 / 2
Question B
3 x² = 49
x² = 49 / 3
x = ± â (49/3)
x = ± 7 / â3
x = ± 7â3 / 3
2007-03-05 02:49:48
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
(A) 4x² - 9 = 0
x² = 9/4
x = \/9/4
x = 3/2
<>
(B)3x²=49
x² = 49/3
x = \/49-:-\/3
x = 7 over \/3
x = 7\/3 / (\/3)²
x = 7\/3 / 3
<>
2007-03-05 01:50:59
·
answer #4
·
answered by aeiou 7
·
0⤊
0⤋
A) 4x^2 -9 = 0
x^2 = 9/4
x^2 = 2.25
x =+/-SQRT(2.25)
x = +/- 1.5
B)3x^2 = 49
x^2 = 16.333333333333
x = +/- SQRT(16.333333333333)
x = +/-4.041451884
or +/- 4.052 (3 dp)
2007-03-05 02:00:34
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
the answer for (a) is:
3/2
-add 9 to both sides
-take sqrt of both sides
-you get 2x=3
-divide both sides by 2
do the same for (b)...
-i would divide by 3 first on this one
-left with x^2=49/3
-then sqrt both sides
answer: x=sqrt(49/3)
2007-03-05 01:48:46
·
answer #6
·
answered by maximusforlife 2
·
0⤊
0⤋
4x^2 - 9 = 0
4x^2 = 9
take square root of both sides
2x = 3
x = 3/2 = 1.5
-------------------------
3x^2 = 49
take square root of both sides
(rt3)x = 7
x = 7 / rt3
2007-03-05 01:47:56
·
answer #7
·
answered by nUssie.. 2
·
0⤊
0⤋